Isopach Map of Mishrif Formation in Nasiriya Oil Field by Using 3D Seismic Data - Habeeb, Yousif T.; Ali, Kamal K. (Iraqi Journal of Science, 2024)
The current study included interpretations of the three-dimensional seismic Data for the Nasiriya oil field implemented by the Oil exploration company in 2010 with a planned surface coverage area of 1273 km². The Nasiriyah field is located in southern Iraq within the Dhi Qar Governorate, about (10) km northwest of the governorate center (Nasiriyah), and the Muthanna governorate is located in the northwestern part of the field, which is approximately (15) km west of the governorate center (Samawah). The information from the wells (well velocity survey, formation depths, logs) was relied upon and entered into the seismic cube data to capture the top of the Mishrif Formation. In addition is to pick the top of the Rumaila Formation, which represents the bottom of the Mishrif Formation. The top and bottom Mishrif reflectors were picked, interpreted, and tracked within the region. The reflector's two-way time (TWT), velocity, and depth maps showed structural closure features in the center of the area, and the general direction of the closure is thenorthwest–southeast. The structural maps showed a general tendency towards the northeast. The isopach map showed that the thickness values of the Mishrif Formation increased to the west and northwest while the thickness decreased toward the east and southeast.